(untitled) (World Bulletin of Public Health, 2022)
Cervical cancer is one of the most serious threats to women’s health. This is the fourth most common cancer in women around the world. According to the forecasts of international experts (taking into account population growth and an increase of life span expectancy), the increase in the incidence and prevalence of cervical cancer will have made up 40% in developing countries and in economically developed countries - 11% by 2020. In the case of nonconducting timely measures for the prevention and treatment of cervical cancer, malignant neoplasms of the cervix will affect up to 1 million women annually after 2050 in the world